PENGARUH MODEL PEMBELAJARAN CORE DISERTAI MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATERI PROTISTA - Hardigalu, Basuki; Yeni, Laili Fitri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effect of CORE learning model with Mind Mapping on student learning outcomes at the Protists material in class X SMA Taruna Bumi Khatulistiwa. This research forms are Quasi Experimental Design with Nonequivalent Control Group Design. This sample consist of two classes of grade X Science 1 as an experimental class and X Science 2 as the control class. Based on the result of the data analysis, the average score of student learning outcomes are taught using the CORE learning model accompanied Mind Mapping at 16.06 while those taught using conventional learning at 13.47. After U Mann-Whitney test of level Î± = 5% obtained Zcount < -Ztable (-4.05 < 1.96), there are significant differences between the learning outcomes are taught using CORE learning model accompanied Mind Mapping by using conventional learning models. Price of effect size obtained relatively high at 1.06 means CORE learning model accompanied Mind Mapping accounted at 35.54%. This explain the CORE learning model accompanied Mind Mapping have effect on student learning outcomes at the Protists material.Â Â Keywords : CORE learning model, Mind Mapping, Protists, learning outcomesÂ